The Attorney General’s Discretion and the Constitutionalityof the Termination of Investigations in the Interest of State Revenue - Guruh Wicahyo Prabowo; Wardana, Dodi Jaya; Toetik Rahayuningsih; Maradona Maradona (Universitas Semarang, 2025)
This study examines the constitutionality and legal boundaries of the Attorney General’s discretion to terminate investigations in the interest of state revenue. The issue arises from the tension between fiscal policy objectives and the constitutional principles of legality, due process, and equality before the law. Using a normative juridical method with statutory, conceptual, and case approaches, the research analyzes the legal framework under Law No. 16 of 2004 as amended by Law No. 11 of 2021, the Criminal Procedure Code, and relevant jurisprudence. The findings indicate that while the Attorney General’s discretionary power to halt investigations can be justified to protect state finances, its implementation currently lacks clear statutory parameters, judicial oversight, and public transparency. This gap creates potential conflicts with constitutional guarantees and risks institutionalizing impunity. The study contributes novelty by constructing a constitutional framework for prosecutorial discretion that aligns fiscal interests with legal certainty and justice. It recommends legislative reform to establish explicit criteria, judicial review mechanisms, and accountability systems to ensure that the Attorney General’s discretion operates within the rule of law and upholds constitutional rights.